Vitamin D levels in children with familial Mediterranean fever. Issue 1 (December 2016) - Onur, Hatice; Aral, Hale; Arica, Vefik; Bercem, Gamze; Kasapcopur, Ozgur
Abstract Background This study aimed to determine whether vitamin D deficiency is more common in children with familial Mediterranean fever (FMF) than in healthy individuals. Methods The study group consisted of 100 patients diagnosed with FMF and 50 healthy children. Serum baseline 25-hydroxyvitamin D levels and other related parameters were evaluated. Results The mean (standard deviation [SD]) vitamin D levels in patients with FMF and healthy controls were 24.78 (8.35) and 28.70 (11.70) ng/mL, respectively. Patients with FMF had significantly decreased vitamin D levels compared with those in healthy controls (P  = 0.039). Vitamin D levels were similar in patients with FMF with differentMEFV mutations (P  = 0.633). Age was significantly correlated with vitamin D levels (r  = −0.235, P  = 0.019). In addition, a negative correlation between parathyroid hormone and vitamin D levels was detected (rs  = −0.382, P  < 0.0001). Conclusion This study demonstrated that vitamin D levels are lower in children with FMF than in healthy controls. We speculate that vitamin D levels should be carefully examined, and nutritional supplementation may be required in patients with FMF. Further studies with larger patient populations are needed to confirm the frequency of vitamin D deficiency in patients with FMF.